Influencia de la sombra sobre el crecimiento y la productividad de las hojas de Vigna sinensis L. - Schoch, Paul-Gérard; Candelario, Luis Santos (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Leaf growth (surface, dry matter, number of epidemic cells) is studied through samplings effected twice a day. Various stages of leaf growth are thus determined, as well as leaf productivity during the day and the night. Importance of photosynthesis, respiration and inner migrations is function of leaf age and radiation. The result indicates that the senescence of leaves is a consequence of lack of radiation. Shade increases the leaf surface, the number of epidermic cells but not the cell surface. Shade decreases also the number of stomata per mm2 and the percentage of stomata in relation to other cells.